Revisiting the holstein-primakov transformations - Gladkov, SO (Annals of Mathematics and Physics, 2023)
It is shown that in addition to the Holstein-Primakov transformations in the theory of magnetism, a number of other transformations can be proposed which also lead to very interesting and consistent results. In particular, with the help of the transformation proposed in the paper for spin operators, it turns out to be possible to strictly analytically calculate the temperature dependence of the ferromagnet magnetization in a wide temperature range from zero and up to the Curie temperature. It is shown that for these transformations in the Curie temperature area, the magnetization tends to zero exponentially. Thus, the aim of this study is to describe magnetization over a wide range of temperatures using a new transformation for electron spin operators.